2011
DOI: 10.4161/cc.10.22.18106
|View full text |Cite
|
Sign up to set email alerts
|

Mdp3 is a novel microtubule-binding protein that regulates microtubule assembly and stability

Abstract: Microtubule-binding proteins are a group of molecules that associate with microtubules, regulate the structural properties of microtubules, and thereby participate in diverse microtubule-mediated cellular activities. A recent mass spectrometry-based proteomic study has identified microtubule-associated protein 7 (MAP7) domain-containing 3 (Mdp3) as a potential microtubule-binding protein. However, its subcellular localization and functional importance are not characterized. In this study, by GST-pulldown assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 21 publications
4
41
0
Order By: Relevance
“…Strikingly, depletion of DDA3 or Mdp3 increased the level of Mdp3 or DDA3 in the complex, respectively. In agreement with previous findings (Sun et al, 2011), endogenous Mdp3 was localized to the mitotic spindle from prometaphase to anaphase (Fig. 1D) and colocalized with DDA3 at the spindle during metaphase (Fig.…”
Section: Results and Discussion Mdp3 Forms The Dda3 Complex During MIsupporting
confidence: 80%
See 1 more Smart Citation
“…Strikingly, depletion of DDA3 or Mdp3 increased the level of Mdp3 or DDA3 in the complex, respectively. In agreement with previous findings (Sun et al, 2011), endogenous Mdp3 was localized to the mitotic spindle from prometaphase to anaphase (Fig. 1D) and colocalized with DDA3 at the spindle during metaphase (Fig.…”
Section: Results and Discussion Mdp3 Forms The Dda3 Complex During MIsupporting
confidence: 80%
“…S1A). Although Mdp3 has been identified as a spindle-associated protein through proteomic analysis (Sauer et al, 2005;Sun et al, 2011), its mitotic function has not been characterized. Hence, we asked whether endogenous Mdp3 and DDA3 form a complex during the cell cycle.…”
Section: Results and Discussion Mdp3 Forms The Dda3 Complex During MImentioning
confidence: 99%
“…Many microtubule-associated proteins (MAPs), such as Mdp3, Dysferlin, Furry, and MST2, are reported to increase microtubule stability by regulating MT acetylation. [40][41][42][43] Therefore, we propose that EWSR1 is a new MAP that can regulate MT acetylation in spindles, along with MT stability and density.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to promote the assembly and stability of microtubules in vitro as well as in cells [25], [26]. MAP7D3 has two potential coiled coil motifs at the N-terminus and it was shown that these coiled coil motifs constitute the microtubule binding region of the protein, although the effects of the microtubule binding region on microtubule polymerization and stability are not known [26]. Interestingly, the N-terminal conserved region has a common function in the proteins MAP7 and MAP7D3.…”
Section: Introductionmentioning
confidence: 99%